THE INTRODUCTION OF COMICS ABOUT RUSSIAN-UKRAINIAN WAR IN EDUCATIONAL PROCESS - Derkachova, Olga (Mountain School of Ukrainian Carpaty, 2025)
The article deals with the study of Ukrainian comics devoted to the russian-Ukrainian war and their introduction in educational process. Creating a new modern reading space is an important problem today, especially after the full-scale russian invasion of Ukraine. Comics already become a part of the Ukrainian reading space, their creation is suggested by teachers to students like a task in lessons, and they are becoming more and more popular. The paper examines the history of the development of Ukrainian comics from the first to the latest, and analyzes the thematic and topical segments. The main focus is on “The Cyborgs” comics, social comics from Inker, educational projects “enWar Mental”, and “We'll Be Back Soon...”. Their plots, structure, and graphic design were analyzed. Each of them is based on real events. The series of comics “The Cyborgs” describes some episodes of the struggle for the Donetsk airport in 2014-2015, during which our defenders began to be called cyborgs for their courage, bravery, and strength. All the events and characters are real. The plots are based on the stories of the direct participants of those events. Inker comic series are also based on real events after February 24, 2022. The main heroes are the Ukrainians who resist the occupier, impress with their heroism and ability not to lose themselves in the war. “enWar Mental” (about the ecological consequences of war) and "We will soon return" (about forced migrants) are not comics in the classical sense, but rather educational projects, as the didactic component plays an important role in their stories: in the first one, the emphasis is on the formation of an eco-responsible personality, in the second on information hygiene and rules of conduct in the information space during war. Conclusions are made about the importance and necessity of introducing these comics into the Ukrainian educational process.